"FRONTLINE HEROES: A NURSE, PHARMACIST, PUBLIC HEALTH TECHNICIAN, BIOMEDICAL SPECIALIST, AND X-RAY TECHNICIAN'S CONTRIBUTIONS TO HEALTHCARE IN SAUDI ARABIA" - Abdulaziz Salah H Alanazi, Saad Hamdan Malouh Alanazi, Abdulkreem Hutail Muklif Alenzy, Salah Sabbar Aldhaferi, Ahmed Lafi Mohammed Almutairi, (Chelonian Research Foundation, 2022)
The healthcare system in Saudi Arabia relies on the dedication and expertise of various healthcare professionals working together to provide quality patient care. This study aims to highlight the contributions of five frontline heroes: a nurse, pharmacist, public health technician, biomedical specialist, and X-ray technician. Through a qualitative approach, semi-structured interviews were conducted with these professionals to gain insights into their roles, challenges, and the impact of their work on patient outcomes. The findings emphasize the importance of interprofessional collaboration, continuous training and development, and the adoption of advanced technologies in enhancing healthcare delivery. The study concludes with recommendations for policy makers and healthcare organizations to support and empower these frontline heroes in their pursuit of excellence in patient care. Keywords: healthcare professionals, Saudi Arabia, interprofessional collaboration, patient care, qualitative research